Appreciative Inquiry for Strategic Planning: An Evaluative and Exploratory Case Study of Two Colleges - Saretsky, Kelly (Graduate Studies, 2013)
This case study attempts to analyze and assess the experiences of two colleges, both of which have chosen and used Appreciative Inquiry (AI) as their strategic planning methodology. These institutions are The College of the North Atlantic/Qatar (CNAQ)—in Doha, Qatar—and Northern Essex Community College (NECC)—in Haverhill, Massachusetts. The specific purposes of this study were to collect empirical data as an objective assessment of AI’s overall effectiveness; to isolate and define the recurring themes which seemed to have contributed to the success—or the lack of success—of this planning methodology; to identify other impacts that AI may have had on these two college’s communities and campus cultures; and, to look for factors that could potentially lead to the expanded and sustained us of AI within these different environments. The results of the study indicate that Appreciative Inquiry has been an effective strategic planning process as experienced by these two colleges: 91% of NECC survey respondents and 90% of CNAQ survey respondents (90% overall) felt that the process resulted in meaningful future directions for the colleges. A large majority of participants (85% for NECC, 75% for CNAQ, 79% overall) also responded favorably to the planning process itself: they felt that the process was a good use of their time; that they could see their contributions in the plan; that they learned something new and valuable about their colleagues; that the process helped them feel excited about the future of the college; and, that they had sufficient opportunity to participate. The major themes which seem to have contributed to the success of the methodology included AI’s inclusive and collaborative nature; the positive, strengths-based and solution-focused mind set; and, the energy and enthusiasm created through working collaboratively toward a preferred future. Finally, a model is presented at the conclusion of the study, which attempts to define the most critical factors necessary for the effective utilization of AI—to ...